Inisiatif Kerima Puri Dalam Implementasi Program Karbon Hutan Berau (PKHB) Di Kampung Merabu - Rizky Rachmadiani; Frentika Wahyu Retnowatik; Tendy (Jurnal Sosial-Politika, 2021)
Kerima Puri is an initiative by the indigenous people of Kampung Merabu to implement PKHB. The type of research used in this research is descriptive. Data collection techniques used in this research is library research. The type of data used is secondary data. The analysis technique used is qualitative. In this study, the researcher used the Local Wisdom Theory to analyze the topic. The results of this research indicate that the Kerima Puri’s initiative resulted in four main programs, the Monitoring of Village Forest Areas, the Development and Utilization Sector for Ecotourism and Environmental Services, the Sector for Utilizing Non-Timber Forest Products, and the Sector for Improving Community Livelihoods (Forestry Agricultural Development).